Increased gender-based violence during the COVID-19 pandemic - Sakinah, Luthfiatus (BKM Public Health and Community Medicine, 2021)
Objective: This paper describes the high number of gender-based violence (KBG) cases during the Covid-19 pandemic and its handling efforts based on a literature review. KBG against women is any act that causes or has the potential to cause physical, sexual, and psychological suffering to women (UN WOMEN, 2020). Many cases of gender-based violence occur in domestic violence (kekerasan di dalam rumah tangga), especially among women. According to WHO data (2018), about 1 in 3 (35%) women worldwide have experienced violence. Globally, 243 million women aged 15-49 have experienced physical and sexual violence by a partner during the pandemic. Cases of violence against women in 2020 in Indonesia reached 50% in the household. The most common forms of violence are physical 31%, sexual violence 30%, psychological violence 28%, and economic violence 10%. Cases of cyber ​​gender-based violence (KBGS) increased by 92% in 2020 compared to 2019. However, overall, victims of violence in 2020 decreased by 31.5% compared to 2019 (CATAHU, 2020). This does not mean that violence cases against women have fallen but are influenced by victims being near perpetrators during the pandemic. Victims complain to their families or remain silent; technological literacy issues and online complaint service models are not yet ready (Bappenas, 2020). Efforts to prevent KBG are an adequate online complaint service and its follow-up services. Conclusion: Gender-based violence needs attention, especially cyber gender-based violence, which has increased during the pandemic.